Evaluation of Oral Health conditions of children and adolescents at the F.F. Soren Baptist Home and Caregivers’ perception of oral hygiene guidelines (Research, Society and Development, 2022)
Lar Batista Francisco Fulgencio Soren is a social shelter institution that aims to care for children and adolescents who are visibly at risk. This experience report aimed to evaluate the oral health conditions of children and adolescents from Lar Batista, and the caregivers' perception about oral hygiene orientations. Questionnaires were conducted with the caregivers, and the children's oral cavity was evaluated through the application of epidemiological forms, in addition to lectures and oral hygiene instruction with this public. It was concluded that social caregivers have great influence in the lives of these children, since they are responsible for contributing to the prevention of oral diseases, besides helping to motivate children to develop oral hygiene habits. As for the children, a high rate of caries disease and other alterations in their oral cavities was noticed, making it important to reinforce oral hygiene instructions and dental care to minimize the problems found.